Penerapan Blended Learning Untuk Peningkatan Kemandirian Belajar Dan Critical Thinking Mahasiswa - Farida, Anisatul; Indah, Ratna Puspita (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2018)
This study aimed to improved understand independency enhancement and critical thinking of learning students through based blended learning. This research combines classroom action research which refers to Stephen Kemmis and Robin Mc Taggart. This research subject were students of engineering information STMIK Duta Bangsa period 2017 / 2018. This research was conducted in two cycles and each cycle was done in two meetings. Every cycle consisted of 4 steps are preparation, action, observation, evaluation, analysis, and reflection. The subject of this research is the students who took Calculus 1. The technique of collecting data was done by assessing test result and observation, test instrument, observation sheet, and field notes. The data was analyzed by using quantitative-descriptive approach. The study showed that the strategy of blended learning proved to be succeeded in increasing understand independency enhancement and critical thinking of learning students through based blended learning in Calculus 1. This is based on the occurrence of (1) increasing of independency enhancement a rise in their ability college student in learning one who is an independent study prior to the adoption of blended learning is as much as 11,2 % and after the cycle of come to an end the application of blended learning was recorded at 88,8 %. (2) increasing in their ability college students to critical thinking between prior to the adoption of blended learning is as much as 12,4 % and over the course of his shift to be over the application of a notebook detailing the development strategy blended learning was recorded at 91,2 %Keywords: Blended Learning, independent learning, critical thinking